PERENCANAAN PENDIDIKAN DALAM KONTEKS MANAJEMEN PENDIDIKAN ISLAM: INTEGRASI NILAI ILAHIAH DALAM MERANCANG MASA DEPAN LEMBAGA PENDIDIKAN - Benny Apero; Fahrurroji; Asmendri; Milya Sari; Husnani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Educational planning is the most fundamental and determinant management function for the success of an educational institution. In the context of Islamic Educational Management (IEM), planning is not merely interpreted as a technical- procedural process to achieve worldly efficiency and effectiveness, but rather as a strategic worship based on divine values to realize a complete educational vision. This article aims to examine in depth the concepts, principles, stages, and models of educational planning from the IEM perspective. This study uses a library research method with a qualitative descriptive-analytical approach. Data were collected from primary and secondary sources such as the Qur'an, Hadith, books, scientific journals, and relevant articles, then analyzed critically to present a comprehensive synthesis. The research findings indicate that Islamic educational planning is visionary, integrative, and holistic. It is based on the principles of Tawhid (directing all ultimate goals to Allah), Sharia (as a normative guide), and Maslahah (for the benefit of the community). The planning process integrates values such as sincerity, basmalah (prayer), istikhārah (communion), shūrā (deliberation), and tawakkal (religious trust). Needs analysis encompasses not only material-intellectual aspects but also spiritual-moral ones. The formulation of objectives is derived from the ultimate goal of Islamic education (tālib al-'Ilm al- Nāfi'), which is to form a perfect human being. This article concludes that Islamic educational planning is a dynamic framework that combines the sophistication of modern strategic planning with the sharpness of Islamic spiritual vision, thus producing an educational "roadmap" that is not only smart (specific, measurable, achievable, relevant, and time-bound) but also blessed (barakah).